The Prevention of Infections in Older Adults: Vaccination. Issue 1 (15th October 2019) - Coll, Patrick P.; Costello, Victoria W.; Kuchel, George A.; Bartley, Jenna; McElhaney, Janet E.
Abstract : All living beings are at risk for experiencing infections; humans are no exception. The prestige and credibility of modern medicine is built in large part on achievements in preventing and treating infectious diseases. For most of human history, there was little that could be done to prevent and treat infections. Millions of humans, of all ages, have died from infections; and in some parts of the world, infection‐related deaths remain common. Advances in preventing and treating infectious diseases include improved sanitization, sterilization, pasteurization, immunization, and antibiotics. Vaccination has played a major role in the prevention of lethal diseases, such as smallpox, diphtheria, cholera, and influenza. Because of developing or waning immune function, the young and the old are at particularly high risk of experiencing infections. Influenza and pneumonia remain common causes of death in older adults. Influenza, in particular, has the potential to result in premature mortality for all age groups, including those who are older and particularly those who live in congregate settings. Vaccination is important in promoting healthy aging. J Am Geriatr Soc 68:207–214, 2019